Gastric cancer; actualities and perspectives of early diagnosis and targeted therapy - Adrian Silaghi; Laura Florentina Rebegea; Daniela Gabriela Balan; Anca Dumitriu; Stana Paunica; Cristian Balalau; Stefăniță Tenea Cojan; Dragos Epistatu; Vlad Denis Constantin (Journal of Mind and Medical Sciences, 2023)
Gastric cancer is an extremely aggressive form of malignancy that, if left untreated, is life-threatening. Improved survival rates depend on early detection of the disease, as well as on the combination of different forms of treatment (surgery, chemotherapy, radiotherapy, immunotherapy, etc.). Screening methods have brought real benefit in early detection of malignancies, but many cases are still diagnosed at advanced stages. The current study is a review related to actualities and perspectives of early diagnosis and targeted therapy of gastric cancer. After an extensive review of the literature, epidemiological, diagnostic and treatment data are presented. The open surgical approach is used in emergency centers or with a low surgical activity, while the minimally invasive approach (laparoscopic, robotic) is possible in large centers dedicated to the treatment of gastric cancer. In the near future, new diagnostic and therapeutic tools are expected to appear, not only to cure cancer definitively, but also to be able to prevent it, if possible, without radically changing the lifestyle of the population.